(untitled) (Comparative & International Education Series, 2021)
This chapter explores how Asian female scholars have faced gendered academic transnationalism in their everyday lives and career. The chapter also provides research trends on perspectives of inherently gendered and uneven academic migration and through synthesizing existing literature. Prior studies report several benefits of the foreign-born scholars’ transnationalism have brought bringing to the US higher education institutions (e.g., enhancing academic productivity and recruiting more international students from home countries to American universities). However, the life course, the familial relations, and long but hardly changed gendered images of Asian female scholars at both their academic institutions and everyday lives needs to be also discussed.